Bangladesh : internal dynamics and external linkages - Abul Kalam (Dhaka, Bangladesh : University Press Ltd., 1996)
Contributed articles.
Includes bibliographical references and index.
Keywords: Bangladesh -- Economic conditions; Bangladesh -- Politics and government -- 1971-; Bangladesh -- Social conditions; Bangladesh -- Economic policy